Human telomerase reverse transcriptase expression in ovarian tumors - Awadh Ali Makhashen Maraei; Ahmad Zailani Hatta; Mohd Sidik Shiran; Geok Chin Tan (Wolters Kluwer Medknow Publications, 2012)
Background : Ovarian cancer is the 6 th most common cancer among women. In ovarian tumors, the borderline category is not well defined due to the difficulty in assessing stromal invasion. The World Health Organization (WHO) defined it as tumor that lacks obvious invasion of the stroma with mitotic activity and nuclear abnormalities intermediate between clearly benign and unquestionably malignant. Telomerase is expressed in many human cancers and is hence a potential biomarker for cancer. Immunohistochemical study of anti-human telomerase enzyme reverse transcriptase (hTERT) antibody allows direct visualization of its expression. The aim of this study was to determine the expression of hTERT and serum CA-125 level in ovarian epithelial tumors, and their ability to distinguish borderline tumor from malignancy. Materials and Methods : This was a retrospective study on 68 ovarian epithelial tumors, comprising of 41 cystadenocarcinoma, 22 borderline tumor and five cystadenoma. By immunohistochemistry, hTERT expression was graded as negative (0-10%), focal (11-25%), regional (26-75%) and diffuse (>75%) positivity. Results : hTERT protein expression in ovarian cystadenocarcinoma, borderline tumor and cystadenoma were 71.4%, 59.1% and 0%, respectively. hTERT and CA-125 had a linear relationship with tumor grade and stage. hTERT protein is detected as large granules/speckled in the cytoplasm and nuclei of ovarian tumors. Conclusions : hTERT protein was highly expression in ovarian epithelial carcinoma. However, the difference between carcinoma and borderline tumor was not statistically significant (P-value = 0.51). It is not an independent biomarker to differentiate borderline tumor from malignant tumor. We suggest using the combination of hTERT immunohistochemistry and serum CA-125 to evaluate difficult situations where histological evaluation fails to distinguish malignant from borderline ovarian tumor.